The “Patient’s Empowerment rights-duty Charter”: new communication tools targeted at patient and professionals in a Hematology and Bone marrow transplant center - Mengozzi, Cipriana; Campaniello, Giovanna; Aversa, Franco; Re, Francesca; Calatafimi, Barbara; Albertini, Roberto; Montali, Francesca (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Empowerment is very important to keep high staff motivation and attention on patient safety. The aim of this study was to produce a “Charter of Rights-Duties for Patients’ Empowerment”, by developing empowerment both of patients and professionals of the Hematology and Bone marrow transplant center Unit of Parma University Hospital. Methods: The professionals were actively involved in meetings to complete the Italian version of the SESM Empowerment Questionnaire, draft the Charter and produce some communication tools to be implemented in the Unit. Results: All professionals had participated to the research. The level of empowerment in the unit, both for doctors and non-medical staff, is very high. This result, the Charter and the others communication tools are now known and shared by all. Conclusions: Stimulating empowerment seems to be a winning choice. It is important to involve professionals right away in the process because a high level of staff empowerment can generate a good field for high degree of patients’ empowerment, that can increase patient safety and reduce the risk of dangerous health choices. This approach aims to increase patient safety through the collaboration of patients, volunteer associations and professionals. Communication programs must include the development of empowerment: it motivates citizens to engage and the literacy enables them to make informed and reasoned choices. General Management is now evaluating how to realize the program in each ward, discussing the importance of carefully conceptualizing this approach for the design of health interventions.